2004
DOI: 10.1093/ps/83.10.1688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Conjugated Linoleic Acid on the Productivity of Laying Hens and Egg Quality During Refrigerated Storage

Abstract: Five hundred and four 40-wk-old Brown Dwarf hens (1.51 +/- 0.08 kg BW) were fed corn-soybean meal diets containing 0, 1, 2, 3, 4, 5, or 6% conjugated linoleic acid (CLA) for 56 d to measure the effects of dietary CLA on laying hen productivity and egg quality during refrigerated storage. Four hens were placed in 1 cage, and 3 cages were grouped as 1 replicate resulting in 6 replicates per treatment. After feeding the experimental diets for 11 d, eggs were collected to determine the fatty acid composition of eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
42
0
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 21 publications
12
42
0
9
Order By: Relevance
“…The increase in yolk weight of eggs from hens fed CLA was much higher than the control group . A recent study showed that dietary CLA increased yolk water content linearly (Shang et al, 2004). Similarly, in the present study, when eggs from CLA-fed laying hens were stored at 4 °C for 30 days, there was a significant increase in the proportions of yolk weight and a decrease in the proportions of albumen compared to the control group.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The increase in yolk weight of eggs from hens fed CLA was much higher than the control group . A recent study showed that dietary CLA increased yolk water content linearly (Shang et al, 2004). Similarly, in the present study, when eggs from CLA-fed laying hens were stored at 4 °C for 30 days, there was a significant increase in the proportions of yolk weight and a decrease in the proportions of albumen compared to the control group.…”
Section: Discussionsupporting
confidence: 83%
“…colour defects and abnormal pH changes in yolk and albumen of eggs) of the eggs stored at 4 °C. As the level of CLA was increased in the diet, yolk pH increased and albumen pH decreased in the eggs stored at 4 °C (Shang et al, 2004). Similar adverse effects were observed in the eggs from laying hens fed cyclopropene fatty acids .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…No mortality of hens occurred during the experiment. Ahn et al (1999) and Shang et al (2004) reported that with increasing dietary CLA supply, feed intake and the rate of egg production decreased linearly. Although initially no significant differences were observed between groups with respect to percentage of egg yolk at one day of storage, there were significant differences between percentage increases of egg yolks at the end of the storage period (Table 3).…”
Section: Resultsmentioning
confidence: 99%